Expanding mental health services in low- and middle-income countries: A task-shifting framework for delivery of comprehensive, collaborative, and community-based care. (27th February 2023) - Bolton, Paul; West, Joyce; Whitney, Claire; Jordans, Mark J.D.; Bass, Judith; Thornicroft, Graham; Murray, Laura; Snider, Leslie; Eaton, Julian; Collins, Pamela Y.; Ventevogel, Peter; Smith, Stephanie; et al.
Abstract: This paper proposes a framework for comprehensive, collaborative, and community-based care (C4) for accessible mental health services in low-resource settings. Because mental health conditions have many causes, this framework includes social, public health, wellness and clinical services. It accommodates integration of stand-alone mental health programs with health and non-health community-based services. It addresses gaps in previous models including lack of community-based psychotherapeutic and social services, difficulty in addressing comorbidity of mental and physical conditions, and how workers interact with respect to referral and coordination of care. The framework is based on task-shifting of services to non-specialized workers. While the framework draws on the World Health Organization's Mental Health Gap Action Program and other global mental health models, there are important differences. The C4 Framework delineates types of workers based on their skills. Separate workers focus on: basic psychoeducation and information sharing; community-level, evidence-based psychotherapeutic counseling; and primary medical care and more advanced, specialized mental health services for more severe or complex cases. This paper is intended for individuals, organizations and governments interested in implementing mental health services. The primary aim is to provide a framework for the provision of widely accessible mental health care and services.